Porosity, strength, and alteration – Towards a new volcano stability assessment tool using VNIR-SWIR reflectance spectroscopy - Gabor Kereszturi; Michael Heap; Lauren N. Schaefer; Herlan Darmawan; Frances M. Deegan; Ben Kennedy; Jean-Christophe Komorowski; Stuart Mead; Marina Rosas-Carbajal; Amy Ryan; Valentin R. Troll; Marlène Villeneuve; et al. (Earth and Planetary Science Letters, 2023)

Detecting the threshold between ornamental landscapes and functional ecological communities: soil microarthropods as indicator species - Valentin Schaefer; Morgan Hocking (Urban Ecosystems, 2015)

Land use intensification alters ecosystem multifunctionality via loss of biodiversity and changes to functional composition - Eric Allan; Pete Manning; Fabian Alt; Julia Binkenstein; Stefan Blaser; Nico Blüthgen; Stefan Böhm; Fabrice Grassein; Norbert Hölzel; Valentin H. Klaus; Till Kleinebecker; E. Kathryn Morris; et al. (Ecology Letters, 2015)
Global change, especially land‐use intensification, affects human well‐being by impacting the delivery of multiple ecosystem services (multifunctionality). However, whether biodiversity loss is a major component of global change effects on multifunctionality in real‐world ecosystems, as in experimental ones, remains unclear. Therefore, we assessed biodiversity, functional composition and 14 ecosystem services on 150 agricultural grasslands differing in land‐use intensity. We also introduce five multifunctionality measures in which ecosystem services were weighted according to realistic land‐use objectives. We found that indirect land‐use effects, i.e. those mediated by biodiversity loss and by changes to functional composition, were as strong as direct effects on average. Their strength varied with land‐use objectives and regional context. Biodiversity loss explained indirect effects in a region of intermediate productivity and was most damaging when land‐use objectives favoured supporting and cultural services. In contrast, functional composition shifts, towards fast‐growing plant species, strongly increased provisioning services in more inherently unproductive grasslands.

Remembering our roots: A possible connection between loss of ecological memory, alien invasions and ecological restoration - Valentin Henry Schaefer (Urban Ecosystems, 2011)